Clinical usefulness of controlled attenuation parameter to screen hepatic steatosis for potential donor of living donor liver transplant. Issue 7 (July 2017) - Hong, Young Mi; Yoon, Ki Tae; Cho, Mong; Chu, Chong Woo; Rhu, Je Ho; Yang, Kwang Ho; Lee, Jun Woo
Abstract : Objective: Hepatic steatosis is associated with an increased risk of graft loss. Although the controlled attenuation parameter (CAP), a process based on transient elastography, has been suggested as a noninvasive method of assessing hepatic steatosis, to date, there is no study on the usefulness of CAP as a single screening tool for detecting hepatic steatosis in potential living donor liver. We evaluated the accuracy of CAP for detecting hepatic steatosis in potential liver donors. Patients and methods: All potential donors of living-donor liver transplantation who underwent a CAP assessment and ultrasonography-guided liver biopsy were enrolled. The steatosis grades were as follows: S0 less than 5%; S1, 5–33%; S2, 34–66%; and S3, more than 66%. Results: According to the liver biopsies, 19 (34.5%) patients had S0, 30 (54.5%) patients had S1, and 6 (11.0%) patients had S2. The CAP value was correlated positively with BMI ( r =0.242, P =0.01), waist circumference ( r =0.268, P =0.006), hip circumference ( r =0.334, P =0.001), Magnetic resonance fat signal fraction ( r =0.465, P =0.001), and histologic steatosis grade ( r =0.542, P =0.001). The area under the receiver operator characteristic curve for the diagnosis of steatosis (≥S2) by CAP was 0.88 (sensitivity 83.3% and specificity 81.6% at a cutoff value of 276 dB/m, P <0.0001). Conclusion: This study suggests that CAP, as a simple and noninvasive preoperative assessment for hepatic steatosis, may be sufficient for identifying and thus excluding significant hepatic steatosis (>33%) in potential liver donors.